2016
DOI: 10.1002/ajh.24572
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for infections in myelofibrosis: role of disease status and treatment. A multicenter study of 507 patients

Abstract: Although infectious complications represent a relevant cause of morbidity and mortality in patients with myelofibrosis (MF), little is known about their incidence, outcome and risk factors. We retrospectively evaluated a cohort of 507 MF patients, diagnosed between 1980 and 2014 in five Italian hematology centers, to define the epidemiology of infections and describe the impact of ruxolitinib (RUX) treatment. Overall, 112 patients (22%) experienced 160 infectious events (grade 3-4, 45%) for an incidence rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…Of note, while hepatitis B serology was performed in most cases (72.6%), the screening for TBC was assessed only in 51.4% of the cases, with one patient that was not investigated for TBC baseline that finally developed a life‐threatening TBC infection. These data reinforce the need for an accurate infectious evaluation of MF patients before the start of ruxolitinib treatment …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Of note, while hepatitis B serology was performed in most cases (72.6%), the screening for TBC was assessed only in 51.4% of the cases, with one patient that was not investigated for TBC baseline that finally developed a life‐threatening TBC infection. These data reinforce the need for an accurate infectious evaluation of MF patients before the start of ruxolitinib treatment …”
Section: Discussionsupporting
confidence: 63%
“…Median reductions in palpable spleen length and TSS were 71.7% and 100%, respectively. A complete resolution of palpable splenomegaly and of TSS was achieved in 24 (34.3%) and 42 (60.0%) patients (Figure 2A (1), disease progression without evolution into acute leukemia (2), infectious complication (bone TBC, 1 case), evolution into acute leukemia (1), and lack or loss of response (6 22,23 There is an ongoing debate on the use of ruxolitinib in intermedi-…”
Section: Spleen and Symptom Responsesmentioning
confidence: 99%
“…Nonetheless, the two cohorts experienced a comparable rate of infectious complications that may be attributed to similar disease severity at baseline. 16 Third, our study failed to detect any significant survival difference between early and overt PMF. It is likely that the inclusion only of patients requiring ruxolitinib therapy selected an early PMF cohort with a more severe disease compared with most early PMF.…”
Section: Discussionmentioning
confidence: 55%
“…Eight papers were excluded for the following reasons: pooled analysis ( n = 1), follow‐up of phase I or II trial ( n = 1), sub‐analyses ( n = 2), data on extension phase study with a shorter follow‐up ( n = 2), redundant publications ( n = 2). Five phase III RCTs (3 phase IIIa with their most recently published extended phase (750 patients) and 2 phase IIIb RCTs (283 patients)), 6 phase IV studies (1524 patients) and 28 case report publications (31 patients, of whom 4 were included also in phase III studies and 1 in phase IV study) were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Six phase IV post‐marketing studies were analysed: their main characteristics are reported in Table . All studies included patients with MF, who received oral ruxolitinib at doses ranging between 5 mg and 50 mg daily.…”
Section: Resultsmentioning
confidence: 99%